Mucosal Vaccination with Recombinant Lactobacillus casei-Displayed CTA1-Conjugated Consensus Matrix Protein-2 (sM2) Induces Broad Protection against Divergent Influenza Subtypes in BALB/c Mice - Chowdhury, Mohammed Y. E. (Public Library of Science, 2014)
To develop a safe and effective mucosal vaccine against pathogenic influenza viruses, we constructed recombinant Lactobacillus casei strains that express conserved matrix protein 2 with (pgsA-CTA1-sM2/L. casei) or without (pgsA-sM2/L. casei) cholera toxin subunit A1 (CTA1) on the surface. The surface localization of the fusion protein was verified by cellular fractionation analyses, flow cytometry and immunofluorescence microscopy. Oral and nasal inoculations of recombinant L. casei into mice resulted in high levels of serum immunoglobulin G (IgG) and mucosal IgA. However, the conjugation of cholera toxin subunit A1 induced more potent mucosal, humoral and cell-mediated immune responses. In a challenge test with 10 MLD(50) of A/EM/Korea/W149/06(H5N1), A/Puerto Rico/8/34(H1N1), A/Aquatic bird /Korea/W81/2005(H5N2), A/Aquatic bird/Korea/W44/2005(H7N3), and A/Chicken/Korea/116/2004(H9N2) viruses, the recombinant pgsA-CTA1-sM2/L. casei provided better protection against lethal challenges than pgsA-sM2/L. casei, pgsA/L. casei and PBS in mice. These results indicate that mucosal immunization with recombinant L. casei expressing CTA1-conjugated sM2 protein on its surface is an effective means of eliciting protective immune responses against diverse influenza subtypes.